Constructing Jesus : memory, imagination, and history - Allison, Dale C. (Grand Rapids, Mich. : Baker Academic, 2010)
"Presenting the fruit of several decades of research, Allison contends that the standard criteria most scholars have employed and continue to employ for constructing the historical Jusus are of little value. His pioneering alternative applies recent findings from cognitive science about human memory to our reading of the Gospels in order to 'construct Jesus' more soundly" -- BOOK JACKET.
The general and the particular : memories of Jesus -- More than a sage : the eschatology of Jesus. Excursus 1 : the kingdom of God and the world to come ; Excursus 2 : the continuity between John the Baptist and Jesus -- More than a prophet : the Christology of Jesus -- More than an aphorist : the discourses of Jesus -- Death and memory : the passion of Jesus -- Memory and invention : how much history?
Includes bibliographical references (p. 463-533) and indexes.
Keywords: Jesus Christ -- Historicity